Mobilizing shame and disgust: abolitionist affective frames in Austrian and German anti-sex-work movements. Issue 3 (2nd September 2019) - Sauer, Birgit
ABSTRACT: This article analyses anti-sex-work mobilization in Austria and Germany since 2014. An affective perspective on the websites of these groups shows how their framings run the risk of establishing a disciplinary regime of governing people, of a restrictive, heterosexist norm of sexuality, and of gender inequality. Abolitionist strategies in the two countries thus produce an affective governmentality excluding those who should not belong to the affective community, i.e. those who do not submit to limiting their sexuality to the private realm of monogamous relationships. Finally, the article suggests that the abolitionist affective mobilisation feeds into the self-affirmation of traditional branches of women's movements in the two countries.